2023
DOI: 10.1001/jamapsychiatry.2022.4435
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Dementia-Related Behaviors Before, During, and After the Pandemic—Disrupting the Behavior-to-Prescribing Reflex

Abstract: Behavioral and psychological symptoms of dementia (BPSD), including depression, anxiety, and psychosis, are ubiquitous among people living with dementia and agnostic to the etiology and stage of illness. 1 Behavioral and psychological symptoms of dementia are associated with poor outcomes for people living with dementia, including reduced quality of life, increased health care use, and nursing home placement as well as worsened caregiver outcomes, including loss of income and employment, increased time providi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Recent research has shown that the antipsychotic prescribing among individuals with ADRD has even increased during the COVID-19 pandemic in multiple countries including France, Italy, South Korea, the United Kingdom, and the United States, 32 which suggests that despite years of regulatory attempts to reduce antipsychotic prescribing, antipsychotics remain the primary treatment providers use to management of BPSD. 33 To reduce inappropriate use of antipsychotics among HHC patients living with ADRD who demonstrate BPSD, they should be provided access to receive behavioral interventions and their family caregivers should be educated on the most appropriate ways to manage BPSD. HHC nurses, while conducting medication review, should be encouraged to report inappropriate or long-term use of antipsychotics to the patient's prescribers to advocate for deprescribing and the use of nonpharmacological interventions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research has shown that the antipsychotic prescribing among individuals with ADRD has even increased during the COVID-19 pandemic in multiple countries including France, Italy, South Korea, the United Kingdom, and the United States, 32 which suggests that despite years of regulatory attempts to reduce antipsychotic prescribing, antipsychotics remain the primary treatment providers use to management of BPSD. 33 To reduce inappropriate use of antipsychotics among HHC patients living with ADRD who demonstrate BPSD, they should be provided access to receive behavioral interventions and their family caregivers should be educated on the most appropriate ways to manage BPSD. HHC nurses, while conducting medication review, should be encouraged to report inappropriate or long-term use of antipsychotics to the patient's prescribers to advocate for deprescribing and the use of nonpharmacological interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Because antipsychotics are not the first‐line therapy for BPSD and their use is associated with adverse outcomes in patients living with ADRD, this finding suggests the possibility of their inappropriate use. Recent research has shown that the antipsychotic prescribing among individuals with ADRD has even increased during the COVID‐19 pandemic in multiple countries including France, Italy, South Korea, the United Kingdom, and the United States, 32 which suggests that despite years of regulatory attempts to reduce antipsychotic prescribing, antipsychotics remain the primary treatment providers use to management of BPSD 33 . To reduce inappropriate use of antipsychotics among HHC patients living with ADRD who demonstrate BPSD, they should be provided access to receive behavioral interventions and their family caregivers should be educated on the most appropriate ways to manage BPSD.…”
Section: Discussionmentioning
confidence: 99%
“…By applying common analytics to multiple databases that cover a large population, we conducted a comprehensive assessment across different health care systems and world regions in a single study. Our study generated initial evidence on the potential antipsychotic use reflex in a timely manner to inform health policy and clinical practice . The study also provides a basis for further in-depth investigations.…”
mentioning
confidence: 99%